The Impact of Mangrove on Water Quality and Milkfish Productivity in The Silvofishery Ponds in Sawojajar Village, Brebes Regency - Novida, Rika; Setia, Tatang Mitra; Santoso, Nyoto; Widigdo, Bambang (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2025)
The mangrove ecosystem plays a crucial role in maintaining coastal ecological balance and providing economic benefits through aquaculture. However, the widespread conversion of mangroves into shrimp ponds has contributed to environmental degradation and increased coastal vulnerability. This study evaluates the effectiveness of the silvofishery system, which integrates mangrove planting with fish farming, in improving water quality and milkfish (Chanos chanos) productivity in Sawojajar Village, Brebes Regency. Three types of ponds were analysed: silvofishery with 40% mangrove vegetation (T40), silvofishery with 20% mangrove vegetation (T20), and conventional ponds without mangroves (T0). Water quality parameters, plankton and benthic diversity, and milkfish growth were measured and compared among the ponds. The results indicate that mangrove-integrated ponds exhibited better water quality stabilization, particularly in terms of salinity, pH, and Dissolved Oxygen (DO), which positively influenced overall ecosystem health. Mangrove vegetation also enhanced fish survival rates and supported long-term ecosystem stability. In contrast, conventional ponds exhibited higher short-term productivity but faced greater environmental risks due to unstable water quality. This study underscores the ecological and economic benefits of the silvofishery system as a sustainable model for coastal resource management.